Paisagem e nostalgia em dois romances de Paulina Chiziane - Pinto, Sandra Fonseca (2022)
This research proposes to analyze the constitution of landscapes, the incarnate subject and the nostalgia present in the novels O alegre canto da perdiz and Niketche: uma história de poligamia, by the Mozambican author Paulina Chiziane. It is based on the thesis that the landscapes constituted in the two novels configure a nostalgic subject. Therefore, the line of reasoning followed in this thesis is guided by the following question: how to articulate the landscapes of the novels with the embodied and nostalgic subject? To this end, the following specific objectives seek to: a) identify the landscapes constituted in the scenes of the two novels from the perspective of the characters' perception. b) to characterize the incarnated subject from the landscapes constituted in the two novels. c) articulate the perceived landscapes with the incarnate subject, to define the nostalgic subject. A bibliographic research was chosen. The choice of corpora was due to the presence of the constitution of landscapes in the perspective of the characters and the narrator, in the two works, which unite the objective space with their subjectivity, and for the existence of nostalgia in the landscapes of the two novels. This investigation uses theoretical contributions from Collot, on the phenomenology of landscape, and from Jankélévitch, Starobinski, Boym and Lourenço, on the concepts of nostalgia. In addition to addressing an overview of African and Mozambican literature and, specifically, the literature of Paulina Chiziane. In order to achieve the objectives outlined, the way in which the objective space joins the individual in a process of intersubjectivity will be examined, which constitutes the incarnated environment as an extension of the subject, as well as the way in which nostalgia is present in the scenes perceived in the novel. The results point to a subject incarnated in his space, who is nostalgic because he seeks to return to a certain place and time in his past.